KEPUASAN KERJA SEBAGAI KUNCI: MEMEDIASI DAMPAK STRES TERHADAP KINERJA KARYAWAN - Putu Gede Arya Nugraha; Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati (Jurnal Bakti Saraswati (JBS), 2025)
This study aims to reveal the role of job satisfaction in influencing the relationship between job stress and employee performance at Bella Resto Canggu.The source of this research includes all employees at Bella Resto Canggu. The sample taken in this study involved 37 employees of Bella Resto Canggu, using the census method. To analyze the data, this study applied multiple linear regression analysis. Data was collected through observation, document review, interviews, and distributing questionnaires. The research findings show that job stress has a negative and significant impact on employee job satisfaction at Bella Resto Canggu. In addition, job stress also has a negative and significant impact on employee performance in the same place. Meanwhile, job satisfaction has a positive and significant effect on employee performance at Bella Resto Canggu and serves as a mediator linking job stress with employee performance. Future research can expand this study by adding other variables that are believed to have an influence on employee performance.